2012
DOI: 10.1590/s1413-35552012005000039
|View full text |Cite
|
Sign up to set email alerts
|

Gait characteristics of younger-old and older-old adults walking overground and on a compliant surface

Abstract: Background: Walking across unstable surfaces disturbs normal stability and efficient strategies must be used to avoid falls. This study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
7
0
3
Order By: Relevance
“…Compared with straight-line gait speed at a comfortable speed, circular gait time at a comfortable speed may be a more sensitive tool to detect the decline in mobility of older adults. A previous study reported that older adults aged >80 years had greater trunk and pelvis sway during walking on a foam surface compared with an old group aged up to 75 years, 24 suggesting that the disability of postural control during walking seems to progress even in old age. In the present study, it is considered that older individuals aged >75 years could not control their posture and coordinate their legs smoothly, 25 resulting in a slower circular gait speed.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with straight-line gait speed at a comfortable speed, circular gait time at a comfortable speed may be a more sensitive tool to detect the decline in mobility of older adults. A previous study reported that older adults aged >80 years had greater trunk and pelvis sway during walking on a foam surface compared with an old group aged up to 75 years, 24 suggesting that the disability of postural control during walking seems to progress even in old age. In the present study, it is considered that older individuals aged >75 years could not control their posture and coordinate their legs smoothly, 25 resulting in a slower circular gait speed.…”
Section: Discussionmentioning
confidence: 98%
“…Gait speed may be used to identify elderly adults at increased risk of early mortality. Slower gait speed is associated with increased risk for falls, and each 10 cm/s decrease in gait speed was associated with a 17% increased risk of falls [ 32 ]. Gait speed is associated with survival among the elderly and reflects health and functional status.…”
Section: Discussionmentioning
confidence: 99%
“…Em contrapartida, os melhores achados em relação ao Conceito Balance também podem ser atribuídos a postulação de maiores esforços para a manutenção da estabilidade corporal, considerando parte de sua execução em superfície instável, o que garante maior necessidade de informações sensoriais 24 . Tal estudo também acrescenta ao referenciar que o treinamento em áreas complacentes favorece o tratamento de neuropatias periféricas, além de distúrbio sensório-motores relativos ao envelhecimento, assim como auxilia na detecção dos mesmos.…”
Section: /9unclassified